Permeable fracture zones in the hard rocks of the geothermal reservoir at Rittershoffen, France. Issue 7 (3rd July 2017) - Vidal, J.; Genter, A.; Chopin, F.
Abstract: Fluid circulation in zones of fractures are a key challenge to exploit deep geothermal heat from natural reservoir. At Rittershoffen (Upper Rhine Graben, France), two geothermal boreholes, GRT‐1 and GRT‐2, were drilled in 2012 and 2014, respectively. They targeted the local Rittershoffen normal fault, which strikes N‐S and dips westward. In this study, major natural fractures were observed in the open holes of both wells from acoustic image logs correlated with other standard geophysical logs (gamma ray, neutron porosity, and caliper). Their permeability was evaluated at the borehole scale from temperature logs, mud losses, and gas surveys. One originally permeable (OP) fracture zone was observed in the granite of GRT‐1. In GRT‐2, four OP fracture zones were observed in the granite and two in sandstones. In GRT‐2, fracture zones are composed by several fluid pathways that could explain the higher natural permeability than in GRT‐1. All OP fractures are associated with positive temperature anomaly, interpreted as circulation of hot geothermal water through the permeable fracture, or negative one, interpreted as the cooling of a porous, altered and fractured zone around the permeable fracture after drilling operations. Permeability of natural fracture oriented N170° seems to be intimately linked to the secondary mineral deposits resulting from paleocirculations. The geometrical fracture model along the wellbore suggests that the inclined trajectory of GRT‐2 increases the connection between the borehole and the nearly vertical fracture network associated to the local fault. A good characterization of zones of fractures in a targeted natural reservoir allows an optimal exploitation of geothermal resource. Key Points: Structural characterization of normal faults and fracture zones from acoustic image logs in two recently drilled geothermal wells Better understanding of natural permeability in a deep hidden granitic basement from thermal profiles Improvement of a conceptual model of fracture zones and fluid circulations at the borehole scale in the Upper Rhine Graben